An Audit of the Patients Treated in Paediatric Surgery Department of Ad-din Womens Medical College Hospital, Dhaka (Journal of Paediatric Surgeons of Bangladesh, 2015)
Background: Surgery without audit is like playing without keeping the score. Medical/Surgical Audit is the evaluation of the quality and efficiency of the surgical services offered to the patients by a group of Medical Personnel in a Hospital. A surgical Audit of the patients of Department of Pediatric Surgery in a non-government Hospital was performed to evaluate overall performance and the quality of service delivered to the patients.Methods: It was a randomized study carried out in the department of Pediatric surgery in Ad-din Womens Medical College Hospital during the period of January 2008 to December 2012 (total 5 years). Total 4613 patients were included in this study. Among them 832 (15.91%) patients were treated after admission and 4396(84.09%) patients were treated as OPD patients.Results: Among the total 4613 patients, 3953 patients were male and 660 patients were female. Total 3127 patients were under 5 years and 1486 patients were over 5 years. Among total 832 admission, 551 (66.22%) were elective cases and 281 (33.78%) were emergency cases.Conclusion: Clinical audit is a process. It is a process used by clinicians who seek to improve patient care. So in this audit we have tried to evaluate our overall performance and the quality of service delivered to our patients in the last 5 years period to find out the limitations and deficiencies prevailing in this field.J. Paediatr. Surg. Bangladesh 3(1): 26-29, 2012 (January)